2000
DOI: 10.1126/science.289.5484.1504
|View full text |Cite
|
Sign up to set email alerts
|

Bone Resorption by Osteoclasts

Abstract: Osteoporosis, a disease endemic in Western society, typically reflects an imbalance in skeletal turnover so that bone resorption exceeds bone formation. Bone resorption is the unique function of the osteoclast, and anti-osteoporosis therapy to date has targeted this cell. The osteoclast is a specialized macrophage polykaryon whose differentiation is principally regulated by macrophage colony-stimulating factor, RANK ligand, and osteoprotegerin. Reflecting integrin-mediated signals, the osteoclast develops a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
2,796
2
97

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 3,478 publications
(2,931 citation statements)
references
References 55 publications
36
2,796
2
97
Order By: Relevance
“…This hypothesis is supported by several observations: first, proinflammatory cytokines, such as TNF␣, IL-1, and IL-6, are found to be systemically up-regulated in RA patients (41)(42)(43). Second, proinflammatory cytokines such as TNF and IL-1 induce a molecule that is pivotally involved in the activation and differentiation of osteoclasts; that molecule is RANKL, which engages its receptor RANK on osteoclast precursor cells (24)(25)(26)(27). Third, serum parameters of bone metabolism reflect an increased bone resorption as the major cause for RA-associated generalized bone loss (14,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This hypothesis is supported by several observations: first, proinflammatory cytokines, such as TNF␣, IL-1, and IL-6, are found to be systemically up-regulated in RA patients (41)(42)(43). Second, proinflammatory cytokines such as TNF and IL-1 induce a molecule that is pivotally involved in the activation and differentiation of osteoclasts; that molecule is RANKL, which engages its receptor RANK on osteoclast precursor cells (24)(25)(26)(27). Third, serum parameters of bone metabolism reflect an increased bone resorption as the major cause for RA-associated generalized bone loss (14,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 79%
“…RANKL stimulates osteoclast differentiation and activation by binding to its receptor RANK on osteoclast precursor cells and mature osteoclasts, thus shifting the balance to an excess of bone resorption (26,27). Osteoprotegerin (OPG) is a naturally occurring decoy receptor of RANKL and blocks its action by preventing RANKL-RANK interaction (28).…”
mentioning
confidence: 99%
“…Attachment of osteoclasts to the bone matrix induces their activation and leads to reorganization of the actin cytoskeleton, formation of sealing zones, and a polarized ruffled membrane juxtaposed to bone. The formation of actin rings is highly characteristic for osteoclasts and is related to their capacity to resorb bone (24,35). It was previously demonstrated that S100A9, in complex with S100A8, promoted polymerization of microtubules, and that S100A9-deficient granulocytes contained significantly less polymerized tubulin (36).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts originate from hematopoietic precursor cells of the phagocyte lineage and differentiate into multinucleated cells by the fusion of mononuclear progenitors (Suda et al 1991). This process consists of multiple steps, including differentiation of osteoclast precursors into mononuclear osteoclasts, fusion of mononuclear preosteoclasts into mature multinucleated osteoclasts and activation of osteoclasts to resorb bone (Boyle et al 2003;Rodan and Martin 2000;Teitlebaum 2000;Chambers 2000). Therefore, natural compounds that specifically inhibit these steps could be developed as anti-resorptive drugs for the treatment of metabolic bone disorders characterized by excessive osteoclastic bone resorption.…”
Section: Introductionmentioning
confidence: 99%